2021
DOI: 10.1007/s13595-021-01026-7
|View full text |Cite
|
Sign up to set email alerts
|

Visual perception of different wood surfaces: an event-related potentials study

Abstract: Key message Visual perception of the appearances of different wood surfaces is greatly influenced by their features, such as color, grain, and gloss. Among these features, human visual perception of wood grain type occurs through a later and higher-ordered cognitive process than the perception of color or gloss. Dark wood was subjectively preferred to light-or medium-colored wood, and both matte and glossy wood were preferred to semigloss wood.• Context Understanding how the appearance of wood is processed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 66 publications
1
16
0
Order By: Relevance
“…This indicates that oak office furniture can be used to generate lower levels of stress amongst office workers. However, it is worth noting that people are more satisfied with dark wood-colored wooden products in terms of product design ( Wan et al, 2021 ); such a difference may stem from the fact that the general product is smaller in size and used alone. Although furniture falls within a category of products, it is bulky and often exists in the building space in combination with other products and fixtures.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that oak office furniture can be used to generate lower levels of stress amongst office workers. However, it is worth noting that people are more satisfied with dark wood-colored wooden products in terms of product design ( Wan et al, 2021 ); such a difference may stem from the fact that the general product is smaller in size and used alone. Although furniture falls within a category of products, it is bulky and often exists in the building space in combination with other products and fixtures.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this was closely related to their unique natural visible characteristics. The wood cells had a substantial amount of their interfaces aligned parallel to the grain, and such interface patterns contribute to the appeal of wood as a material [32].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, pictures of the tiles were used as the stimuli. In an event-related potential study, Wan et al (2021) classified the lightness of stimuli into light, medium, and dark levels, and found that the lightness factor can modulate brain activity. However, the effect of tile brightness on brain activity is still unknown.…”
Section: Methodsmentioning
confidence: 99%